Use of oats and fat in swine grower rations - Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two feeding trials involving 112 Yorkshire weaned pigs (25 lbs.) were conducted to study the use of oats and fat in grower rations. Adding 3% fat (soy oil) to the fortified corn-soybean control ration reduced daily feed intake, but improved feed efficiency. Incorporating 40% oats in a fortified corn-soybean meal grower ration resulted in similar pig performance for rate of gain, daily feed intake, and feed efficiency even though the ration contained 6.5% fiber. Pigs fed a diet containing 40% oats and 5% fat gained 5% faster and were 10% more efficient than pigs fed the control ration.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Oats; Fat; Rations